Evaluation of the impact of alveolar bone graft surgery on the internal nasal dimensions of individuals with cleft lip and palate by means of computed tomography - Nascimento, Maryana Lourenço Bastos do (2024)
Introduction: Cleft lip and palate are the most common congenital malformations in the craniofacial region. They occur with an average prevalence of between 1 and 2 individuals per 100 births. In Brazil, they occur at a rate of 1:700 births, with an estimated 225,000 affected by these alterations. Orofacial clefts cause functional impacts on patients, such as changes in breathing, teeth, speech, chewing, swallowing and sucking. Treatment begins with the primary surgeries, cheiloplasty and palatoplasty, which aim to reconstruct the soft tissue. Secondary alveolar bone grafting (SABG) reconstructs the existing bone defect in the cleft region. The main aim of SABG is to supply bone tissue to the cleft region and give continuity to the alveolar process. Objective: To measure the changes in the cross-sectional areas (CSAs) and nasal volume of patients and their impact on the nasal cavity (NC) in the two-month postoperative period (PO2M). Methodology: The study included 15 patients with complete unilateral transforaminal cleft lip and palate (UCLP) with an indication for ABG. Cone beam computed tomography scans obtained prior to SABG and POS2M were compared. The nasal volumes and cross-sectional areas were obtained by marking the masks delimiting the nasal cavity on the CT scans using the Mimics software. Results: NC volumes (total, right and left sides) are statistically lower at PO2M in patients with left-sided UCLP. In patients with right-sided CLP, these volumes are only significant in the total NC and left NC. The CSAs of the internal nasal valve in both patients showed significantly lower values compared to the preoperative period (p0.05). Conclusion: Alveolar bone graft surgery reduces in the short term the volume of the nasal cavities and the cross-sectional areas of the right and left internal nasal valve as a whole, and not just the area of the cleft where the graft material was placed.